2021
DOI: 10.7150/ijms.50871
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-362 negatively and positively regulates SMAD4 expression in TGF-β/SMAD signaling to suppress cell migration and invasion

Abstract: Cell migration and invasion are modulated by epithelial-to-mesenchymal transition (EMT) and the reverse MET process. Despite the detection of microRNA-362 (miR-362, both the miR-362-5p and -3p species) in cancers, none of the identified miR-362 targets is a mesenchymal or epithelial factor to link miR-362 with EMT/MET and metastasis. Focusing on the TGF-β/SMAD signaling pathway in this work, luciferase assays and western blot data showed that miR-362 targeted and negatively regulated expression of SMAD4 and E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Specifically, Prdm1 appears to be more involved in promoting the resistance against exhaustion in cNK cells, whereas in ILC1s, it may play a role in the plasticity between ILC1s and ILC3s. In both our previous study and a study by Colonna et al (25,67), it was demonstrated that Smad4, a transcriptional factor involved in TGF-β signal pathway, upregulated Prdm1 in NK cells and depletion of Smad4 resulted in a decreased ratio of NK cells to ILC1s in the liver. However, knocking out Prdm1 in Ncr1 + cells increased the ratio of NK cells to ILC1s in liver group 1 ILCs (Figure 2A).…”
Section: Discussionmentioning
confidence: 63%
“…Specifically, Prdm1 appears to be more involved in promoting the resistance against exhaustion in cNK cells, whereas in ILC1s, it may play a role in the plasticity between ILC1s and ILC3s. In both our previous study and a study by Colonna et al (25,67), it was demonstrated that Smad4, a transcriptional factor involved in TGF-β signal pathway, upregulated Prdm1 in NK cells and depletion of Smad4 resulted in a decreased ratio of NK cells to ILC1s in the liver. However, knocking out Prdm1 in Ncr1 + cells increased the ratio of NK cells to ILC1s in liver group 1 ILCs (Figure 2A).…”
Section: Discussionmentioning
confidence: 63%